2015
DOI: 10.1088/1054-660x/26/2/026001
|View full text |Cite
|
Sign up to set email alerts
|

Quantum control of dressed state population for Li2molecules by intense femtosecond laser pulses

Abstract: We investigated the Autler-Townes splitting in photoelectron spectra of Li 2 molecules steered by ultrashort laser pulses using the time-dependent wave-packet method. Structure of the Autler-Townes splitting was presented to analyze the information of a selective population of the dressed states. It was found that population transfer process, structure of photoelectron spectrum and pattern of Autler-Townes splitting can be controlled by adjusting the intensity, wavelength and delay time of laser pulses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The split-operator Fourier method is used to solve the time-dependent Schrödinger equation. [29,30] The population on each electronic state is written as [2][3][4][5][6][7][8][9][10][11][12][13]22,24,25,27,29]…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The split-operator Fourier method is used to solve the time-dependent Schrödinger equation. [29,30] The population on each electronic state is written as [2][3][4][5][6][7][8][9][10][11][12][13]22,24,25,27,29]…”
Section: Theorymentioning
confidence: 99%
“…Hu et al [22] and Yan et al [23] studied the sensitivity of the population transfer and the angular distribution of population of the four-level Li 2 to the molecular rotation. Han et al [24] and Jing et al [25] presented that the laser intensity, wavelength, and delay time affect the state population of the four-level Li 2 . Liu et al [26,27] proposed that the delay time only alters the peaks height, but does not change the peak positions of the photoelectron spectra of Li 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Various properties and phenomena of diatomic molecules have been studied using ultrashort technology, such as population transfer [11], photoionization [12][13][14][15][16][17] and Rabi oscillation [18]. An increasing number of researchers have been focusing on exploring the photoelectron spectroscopy of diatomic molecules and the Autler-Townes splitting (ATS) phenomenon [19][20][21][22][23][24][25][26][27][28][29][30], which was first observed in a sodium atom beam under microwave excitation [31]. * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Laser parameters, such as laser intensity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], laser wavelength [4][5][6][7][8][12][13][14][15][16]18], pulse width [1][2][3][7][8][9][10]18,19], pulse envelope [4,5], and delay time [10][11][12][13][14][15][16][17] can be used for controlling the excitation, ionization and dissociation processes of molecules, and have been studied in multi-level molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [11,12] proposed that asymmetric double peaks arise for longer delay time, the delay time only alters the peak height, but does not alter the peak positions of photoelectron spectra of three-level Li 2 . Han et al [13] suggested there is no AT splitting for weaker pump intensity or longer delay time, the pump wavelength detuning induced the asymmetric AT double splitting for three-level Li 2 . Yao et al [14,15] proposed that the laser intensity, pump wavelength and delay time can control the selective population of dressed states of three-level K 2 .…”
Section: Introductionmentioning
confidence: 99%